O pequeno forasteiro: Novas leis favorecerão a introdução de espécies não-nativas de zooplâncton em ambientes aquáticos Brasileiros - Coelho, Paula Nunes [UNESP]; Henry, Raoul [UNESP] (FapUNIFESP (SciELO), 2017)
Non-native species of zooplankton have been introduced in Brazilian continental aquatic environments for a variety of reasons (e.g., non-native fish stocking, aquaculture), but many pathways of zooplankton introductions remain unknown. Recently, the governor of the State of Amazonas passed Law No. 79/2016, which allows for aquaculture operations using non-native fish in that state. This change in policy will likely result in the species introduction or propagule pressure of non-native zooplankton such as: Mesocyclops ogunnus Onabamiro, 1957; Kellicottia bostoniensis (Rousselet, 1908); Daphnia lumholtzi Sars, 1885; Lernaea cyprinacea (Linnaeus, 1758); Lamproglena monodi Capart, 1944. Of further concern is federal law No. 5989/09, which proposes the use of non-native fish in Brazilian aquaculture nationwide. We believe that both laws will intensify the introduction of non-native zooplankton. Once established in aquatic environments, non-native species of zooplankton could result in negative impacts (e.g., a loss of ecosystem services, food web alterations). Therefore, Brazilian authorities should incentivize the use of local native species rather than pass laws that threaten the environment.
The small foreigner: New laws will promote the introduction of non-native zooplankton in Brazilian aquatic environments
Keywords: Biological invasions; Environmental policy; Freshwater; Neotropical; Propagule pressure